“Perbedaan Rata-Rata Ankle-Brachial Index (ABI) Sebelum Dan Sesudah Dilakukannya Senam Kaki Diabetik Di Wilayah Kerja Puskesmas Simpang Kawat Kota Jambi”. - Hafifah, Hafifah; Rudini, Dini; Sari, Lisa Anita (Jurnal Keperawatan Universitas Jambi, 2025)
Peripheral artery disease (PAD) is one of the chronic complications of type 2 diabetes mellitus that can be identified through the Ankle-Brachial Index (ABI). A low ABI score indicates impaired blood flow in the lower extremities. Diabetic foot exercise is a non-pharmacological intervention that can improve peripheral circulation. This study aimed to determine the difference in average ABI before and after the implementation of diabetic foot exercise in type 2 diabetes patients at the Simpang Kawat Public Health Center in Jambi City. This quantitative research used a quasi-experimental one-group pretest-posttest design. A total of 35 respondents were selected through purposive sampling based on specific inclusion and exclusion criteria. The intervention involved diabetic foot exercises performed twice weekly over a period of one week. ABI values were measured using a vascular Doppler device before and after the intervention, and data were analyzed using the paired sample t-test. The results showed a significant increase in mean ABI scores from 0.89 to 0.94 in both lower limbs. Statistical analysis revealed a significant difference (p < 0.001), and the effect size was large (d = 1.39 for the right extremity, d = 1.28 for the left), indicating the strong effectiveness of the intervention. In conclusion, diabetic foot exercise significantly improves peripheral blood circulation in patients with type 2 diabetes mellitus and can be recommended as part of routine diabetes self-care management.